Rhabdomyomatous mesenchymal hamartoma: a case report - Fernanda Alves Luiz Rodrigues; Maria Auxiliadora de Paula Carneiro Cysneiros; Rubson Rodrigues Júnior; Denis Masashi Sugita (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2014)
The rhabdomyomatous mesenchymal hamartoma (RMH) is a rare type of hamartoma, composed of randomly arranged striated muscle fibers in dermis and subcutaneous tissue, associated with normal mesenchymal elements. Our objective is to report a case of this rare entity that occurred in the nasal dorsum of a 4-year-old child.